The Correlation between the Writing Ability and Self-esteem of Surabaya Merchant Marine Academy Students - Dias, Agata (Widya Mandala Catholic University Surabaya, 2013)
Writing in EFL has been an essential requirement for Students of Surabaya Merchant Marine Academy because it is used when they are on board. Even though it is compulsory, the writing progress is unsatisfactory. Recent studies widely investigate and find the correlation between affective factors in learning, especially self-esteem, and student’s writing improvements. Following the issues, the present study investigated the correlation between Surabaya Merchant Marine Academy students’ English writing progress and their self-esteem. The data were collected using two instruments; Test of English Writing (TEW) and Questionnaire of Self-esteem (QSE) which covers three sections of questionnaire; global, situational and task self-esteem. The instruments were distributed to 107 students. Then the data were analyzed using Pearson Product Moment. Results of the study revealed that the overall scores of TEW indicated that the level of the student’s writing ability was fair; the highest correlation level appeared between situational self-esteem and writing ability and the lowest correlation level appeared between global self-esteem and writing ability, and finally the correlation between self-esteem and writing ability of the students was significantly positive.